Threats and Overcoming Behaviors Experienced by Women Entrepreneurs - Vania Maria Jorge Nassif; Marcos Hashimoto; Cândido Vieira Borges Junior; Edmilson de Oliveira Lima; Jefferson Lopes La Falce (BAR: Brazilian Administration Review)
Objective: this article aims to identify threats experienced by women entrepreneurs and describe the behaviors they use to overcome them so they can continue developing their businesses. Methods: the research is qualitative, exploratory in nature, and semi-structured interviews were used for data collection. Sixty-five entrepreneurs in the Network of Women Entrepreneurs in Brazil participated in the study. Using the Atlas.ti software, a lexicographic analysis identified three types of threats (role conflicts, affective, and patriarchy) and three overcoming behaviors (dialogue and negotiation, use of male vigor network, and resilience). Results: the findings describe the adverse, hostile, and embarrassing conditions women entrepreneurs face in running their businesses and suggest a typology of threats and behaviors to overcome such conditions. Conclusions: this study contributes to the body of research on female entrepreneurship by identifying categories of threats unique to women entrepreneurs. A more comprehensive understanding of this reality contributes not only to better individual actions but also to inspiring the creation of public policies to help women in the continuity and survival of their businesses.